The Phenomena of Pregnancy Out of Marriage Among Students and the Solution - Satrianis Satrianis; Deswana Deswana; Septi Nila Hayati; Abdul Aziz (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
The development of the current era of globalization has had various impacts on every level of society, especially among students, with the influx of foreign cultures causing students to follow this culture, one of which is having free sex which results in the phenomenon of getting pregnant before marriage. Pregnancy out of marriage that occurs among students today is due to a lack of attention or supervision from the family, and is caused by students' curiosity about sexual relations, the consequences of which can destroy their future and aspirations. This study aims to analyze how the phenomenon of pregnancy out of marriage among students. This research uses the method qualitative approach with phenomenology. Sources of data were taken from three informants through in-depth interviews who were selected using the technique of purposive sampling. The results of the analysis show three themes: i) The phenomenon of pregnancy out of marriage among students is caused by three factors, namely: a) behavioral factors: promiscuity b) family factors: lack of parental supervision c) environmental factors: low religious moral education ii) conditions student life after marriage: the economy is borne by the family, the family is not harmonious iii) The student's reasons for getting pregnant out of marriage, namely: curiosity about sexual relations, because of pressure from partners. The results of this study can be used as initial data for future researchers to examine this issue in different contexts and issues.